INTEGRASI EKSTRAKURIKULER PENDIDIKAN ANAK USIA DINI BERBASIS PENDIDIKAN AGAMA ISLAM: - Mufarochah, Siti; Asyrofiyah, Islachiyatul; Khulusinniyah; Mukaromah, Luluk (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Early childhood education is developed creatively through learning development based Islamic Religious Education in extracurricular practices that have been carried out by Nurul Fatah Kalibaru Banyuwangi Kindergarten. Islamic Religious Education learning in kindergarten institutions is learning process whose learning uses an Islamic teaching approach. In this research, the author used qualitative research methods, that is research for describe an event, symptom, and event that occur for now. The results of the research are in every process of extracurricular activities at Nurul Fatah Kalibaru Banyuwangi Kindergarten integrated with the Islamic Religious Education learning system, children are introduce to Islamic teachings from an early age. The Islamic religious education approach in Nurul Fatah Kalibaru Kindergarten was been applied to children’s extracurricular activities outside school hours, including: congregational dzuhur prayers and additional habituation to Islamic activities.